The National Lung Screening Trial: Results stratified by demographics, smoking history, and lung cancer histology. Issue 22 (26th August 2013) - Pinsky, Paul F.; Church, Timothy R.; Izmirlian, Grant; Kramer, Barnett S.
Abstract : BACKGROUND: The National Lung Screening Trial (NLST), which compared lung cancer screening with low‐dose computed tomography (LDCT) versus chest radiography (CXR), demonstrated a statistically significant mortality benefit of LDCT screening. In the current study, the authors performed a post hoc analysis to examine whether the benefit was affected by various baseline factors, including age, sex, and smoking status, and whether it differed by tumor histology. METHODS: Lung cancer death rates were computed as events over person‐years of observation; the mortality risk ratio (RR) was defined as the lung cancer death rate in the LDCT versus CXR trial arms. Poisson regression was used to test for interactions of sex, age (< 65 years vs ≥ 65 years), and smoking status (current vs former) with trial arm. Mortality RRs were also computed for specific lung cancer histologies. RESULTS: The overall mortality RR was 0.92 in men and 0.73 in women, with a P value for interaction of .08. RRs were similar for individuals aged < 65 years versus those aged ≥ 65 years (0.82 vs 0.87), and for current versus former smokers (0.81 vs 0.91). By tumor histology, mortality RRs were 0.75 for adenocarcinoma, 0.71 for all non‐small cell lung cancers except squamous, 1.23 for squamous cell carcinoma, and 0.90 for small cell carcinoma. RRs were similar for men and women for nonsquamous non‐small cell lung cancers (0.71 and 0.70, respectively); women were found to have lower RRs for small cell and squamous cell carcinoma. CONCLUSIONS: A benefit of LDCT did not appear to vary substantially by age or smoking status; there was weak evidence of a differential benefit by sex. A differential benefit across lung cancer histologies may exist. Cancer 2013 ;119:3976–3983. Published 2013. This article is a U.S. Government work and is in the public domain in the USA. Abstract : The benefit of computed tomography screening in the National Lung Screening Trial did not vary substantially by age or smoking status; there was weak evidence of a differential benefit by sex. A differential benefit across lung cancer histologies may exist.